Shedding Further Light on Upper Cretaceous – Neogene Subsurface Lithostratigraphy of Southwestern Iraq - Y. Tamar-Agha, Mazin; E.A. Al-Sagri, Khedar (Iraqi Journal of Science, 2023)
Exploratory activities carried out by oil companies in the latter half of the pastcentury proved the existence of voluminous reserve of oil and gas in thesouthwestern area of Iraq. In view of this, it seemed more than prudent to add a newknowledge to that currently existing about the subsurface lithostratigraphy of thisarea. As a first step in fulfilling this mission, this paper will attempt to do so bycovering the time interval from the Upper Cretaceous to the Neogene. In turn, thiseffort had entailed both the description of about 4707 metres of fully recoveredcores, plus the subjection of more than 4000 samples to existing petrologic analyses.Findings worth mentioning does include the observation that with the exception ofthe Paleogene sequence, the Upper Cretaceous and Neogene sequences are nodifferent from those found in other parts of southern Iraq. For instance, the UpperCretaceous sequence is found to be consisted of the common Hartha, Qurna, andTayarat Formations. The same could be said about the Neogene sequence which isfound to be again made of the common Ghar, Euphrates, Fatha, and ZahraFormations. In contrast, the Paleocene – Lower Eocene sequence lithology is founda bit different from those commonly encountered in other parts of southern Iraq.This difference emanates from the intense sulphidzation as manifested in thecommon occurrence of anhydrite, gypsum, and vanished evaporite being observedthrough the lower Paleogene sediments of south west, Iraq. Because thisphenomena exhibits strong vertical as well as lateral variation, this sequence isdivided into an intensely evaporitic portion, which is introduced in this article underthe name of the Jerishan Group (Paleocene - Lower Eocene), inclusive of Umm ErRadhuma, Rus, Jil/Rus, and Jil Formations. The latter formation is recentlyintroduced stratigraphic rock unit representing the non-evaporitic equivalent for theRus Formation. The less evaporitic portion (the Dammam Formation) of thePaleogene was found to be the same as the ones found in other parts of the southIraq, Kuwait and Saudi Arabia.